Porous Mn doped g-C3N4 photocatalysts for enhanced synergetic degradation under visible-light illumination - Wang, Ji-Chao; Cui, Cheng-Xing; Li, Ying; Liu, Lu; Zhang, Yu-Ping; Shi, Weina (Journal of hazardous materials, 2017)
[Display omitted] •Mn doping and carboxylation increase photocatalytic activity of g-C3N4.•Mn doping improves the charge separation of g-C3N4.•Synergism of photocatalytic Cr (VI) reduction and organics degradation was observed.•The good stability and activity of g-C3N4-Mn-H were found after 7 runs. Photocatalytic degradation by semiconductors is an ideal way to solve the environmental problem. Here, the porous Mn doped g-C3N4 photocatalyst was synthesized by the calcination-refluxing method. The as-prepared g-C3N4 exhibits the high activity of photocatalytic degradation under visible light irradiation ( > 400nm) in the mixed system of Cr(VI) and organic pollutants. Especially, the photocatalytic activity of Cr(VI) reduction was increased from 9.5% to 76.5%, while that of Rhodamine B(RhB) degradation was enhanced from 15.3% to 88.9% after 60min irradiation. The porous Mn doped g-C3N4 still keeps the high degradation efficiency of mixed pollutants in the 7th running. Based on the computational modeling, the Mn doping and carboxyl modification affect the atomic arrangement and molecular orbital distribution of the g-C3N4 semiconductor, leading to the enhancement of photo-induced carrier separation. Additionally, the active oxygen species and intermediates in the photoreaction process were discovered by ESR measurement and UV–vis test. The RhB degradation in synergistic photocatalysis not only inhibits the reverse reaction of Cr(VI) reduction, but also validly supply the photogenerated electrons by the photosensitization effect. This work may be useful for rationally designing photocatalysts and providing illuminating insights into the photocatalytic mechanism.